Transformasi Digital dan Pengaruhnya terhadap Loyalitas Nasabah Bank Syariah - Saiful Bakhri; Frida Auliya A (Universitas 45 Surabaya, 2025)
Digital transformation has become an essential strategy for Islamic banking institutions in improving service quality, operational efficiency, and customer experience. This study aims to analyze the influence of digital transformation on the loyalty of customers within Islamic banks in Indonesia. The research highlights how digital services such as mobile banking, online customer service, and automated sharia-compliant transaction systems affect satisfaction, trust, and long-term customer retention. Using a descriptive qualitative approach, this study reviews theoretical frameworks and previous empirical findings concerning technology adoption, service quality, and customer loyalty in the context of Islamic finance. The analysis demonstrates that effective digital transformation strengthens customer engagement by providing convenience, transparency, and accessibility aligned with sharia principles. Moreover, digital innovation enables Islamic banks to maintain competitiveness in an increasingly digital-driven financial landscape. The implications of this study emphasize the importance of continuous technological development, customer education, and system reliability to foster higher loyalty among Islamic banking customers. This article contributes to the growing literature on digitalization in Islamic finance and provides insights that may guide practitioners in enhancing customer-centered digital strategies.